Facing the 25% unemployment rate. The sad socio-economic panorama of southern Europe - Espínola, José Ramón de (Razón y fe, 2018)
We Spaniards are immersed in a climate of alarm. Our GDP continues to fall and in 2013 the unemployment rate will continue to grow. Recession and unemployment have as an inseparable companion: a large debt. Our spending pattern is dislocated, which brings us closer to financial rescue. Our economy needs very serious adjustments. Undertaking them entails resignations and changes: in short, a reconversion that goes through a financial reform, a balanced adjustment of public finances, a sustainable growth pattern and, finally, clear and determined help from Europe.